Estudio agroproductivo del cultivo de tomate de árbol (Solanum betaceum) en la parroquia Chiquicha del cantón Pelileo provincia de Tungurahua - Carranza Cando, Luciano Fabián (2019)
The present work of investigation approaches the establishment of productive processes for the producers tree tomato of the Chiquicha; to know an adequate management of agricultural and financial resources of the crop, in order to achieve a better productive chain and therefore better economic income that will help families to have a sustainable standard of living, so the title of the study is: "Agroproductive study of the tomato tree crop (Solanum betaceum) in the Chiquicha parish of the Pelileo Canton of Tungurahua Province", once the theme was defined and the variables outlined: agroproductive study and tree tomato cultivation were proposed as objectives: Describe the agroproductive process of tree tomato cultivation in the parish. Analyze the supply and demand of fruit in the local market and propose new marketing strategies; for this, the information gathered in written and digital sources was very helpful. The research work methodology was established based on the survey made to tree tomato growers and interviews with traders, in order to identify the factors that have an impact on the production and commercialization of the product, at the end of the same it was observed that the 55% of the group of producers surveyed are made up of women and 45% are men; the producers are owners of medium-sized plantations mostly (3 to 4 blocks, 53.8%), they have sporadic technical and professional advice in case all the respondents is 67 individuals and are in an economically productive age; where agricultural work is carried out with family and contracted labor, reactivating the productive sector and reducing levels of unemployment in the area. The loss of production of the tree tomato in the area is due mostly to the incidence and severity of pests (nematodes), diseases (chicken eye) and drought, while the low prices paid by intermediaries represent a serious problem during marketing. For the preparation of the soil to implement the tree tomato crop in the area the producer mostly uses hand tools and yokes. The technology used for the planting of tree tomatoes in the area is mostly chemical combined with organic. According to the research, 88.8% of producers spend fertilization from 150 to 450 USD per block during the entire production process. The collection of fruits is done once a week for sale in wooden boxes and the price set for this is based on the market; This commercialization is carried out 95% to the intermediaries, whether they are wholesale or retail merchants and only 5% do it directly to the final consumer without giving added value